Influence of Strategic Agility Practices on the Performance of Deposit Taking Saccos in Nairobi County - Chebet, Joyce (European Journal of Business and Strategic Management, 2024)
Purpose: Most businesses find it to be a challenging task to maintain positive performance always, especially in these current phases of economic meltdown. Therefore, organizations that might survive in this kind of situations are organizations that are flexible, responsive, and dynamic. These features are associated with organizations that are agile coined as Strategic Agility (SA). Overall, the study aimed to assess the impact of implementing strategic agility practices by deposit-taking SACCOS in Nairobi County on their performance. Precisely, the study examined the impact of resource fluidity, corporate governance dimensions and corporate foresight on performance of the Saccos. Methodology: In this research, the theoretical review focused on three theories; socio-technical systems theory, the dynamic capability theory, and the agency theory. The research was descriptive in design and population was drawn from the 57-deposit taking Saccos in Nairobi County. The study included 196 staff members as the total population. Findings: The findings were organized using frequencies, percentages, mean, and standard deviation. Regression analysis assessed the statistical significance of the relationship between specific strategic agility practices and performance among deposit-taking SACCOS in Kenya. The study showed that although resource agility and performance had a favorable relationship, the effect was not statistically significant. The second objective's results showed that corporate governance had a favorable, but statistically negligible, impact on SACCO performance. The study's findings also showed that corporate foresight significantly and favorably affected SACCO performance. Finally, the study demonstrated that inventive capability had a favorable and noteworthy impact on SACCO performance. Unique Contribution to Theory, Practice and Policy: The study also recommended improving planning and communication strategies, particularly when making substantive changes to the organizational culture since clear communication can minimize resistance and ensure smoother transitions. The study further recommended that Saccos should maintain and enhance routine engagements with regulators to identify and address gaps in corporate governance practices which can lead to more robust governance frameworks.